Raymond Loewy papers - Loewy, Raymond, 1893-1986.
Correspondence; administrative, client, and project files; and financial and legal papers relating to Loewy's work as an industrial designer. The collection documents the growth of his company from a small firm to a complex system of international corporations and subsidiaries concerned with architecture, corporate image coordination, exhibitions, marketing, packaging, product design, and other aspects of industrial design. Includes correspondence, speeches, and writings of the Loewy firms' chief executives Joseph Lovelace, James J. Sheridan, William Snaith, and Loewy himself. Prominent clients include Abraham & Straus, Coca-Cola Company, Exxon Corporation, Greyhound Corporation, Higbee Co., John Wanamaker (firm), Liggett & Myers Tobacco Company, Lord & Taylor, Martin Marietta Corporation, Nabisco, Inc., National Aeronautics and Space Administration (Skylab project), Pennsylvania Railroad, Sibley, Lindsay and Curr Company, Studebaker Corporation, U.S. Forest Service, United States Postal Service, and Woodward & Lothrop. Includes files on designs for many other companies and products in the United States, France, Great Britain, Soviet Union, and elsewhere.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Industrial designer. Full name: Raymond Fernand Loewy. Born in France; emigrated to the United States in 1919.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Lovelace, Joseph -- Correspondence; Sheridan, James J., -- 1933- -- Correspondence; Snaith, William, -- 1908-1974 -- Correspondence; Abraham & Straus; Coca-Cola Company; Exxon Corporation; Greyhound Corporation; Higbee Co; John Wanamaker (Firm); Liggett & Myers Tobacco Company; Lord & Taylor; Martin Marietta Corporation; Nabisco, Inc; Pennsylvania Railroad; Sibley, Lindsay and Curr Company; Skylab Program; Studebaker Corporation; United States. -- Forest Service; United States. -- National Aeronautics and Space Administration; United States Postal Service; Woodward & Lothrop; Architecture; Brand name products; Industrial design -- Exhibitions; Industrial design -- Great Britain; Industrial design -- France; Industrial design -- Soviet Union; Industrial design -- United States; Industrial design coordination; Marketing; Packaging; Industrial designers